Dampak Tubo Belerang terhadap Sosial Ekonomi Masyarakat Kawasan Danau Maninjau Nagari Koto Malintang Kecamatan Tanjung Raya Kabupaten Agam - Silvia Silvia; Resdati Resdati (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2025)
Tubo belerang is a term commonly used by local communities to describe the mass fish mortality event occurring in the Maninjau Lake area, which causes significant losses, especially for floating net cage farmers. This study aims to examine the impact of tubo belerang on the social and economic conditions of KJA farmers, as well as to identify the factors that motivate these farmers to continue their fish farming business despite the losses incurred due to tubo belerang. The sociological approach applied in this research includes structural functionalism, social change, and rational choice theory. This study employs a descriptive quantitative research design with data collected through questionnaires and documentation. Sampling was conducted using probability sampling with proportional random sampling, resulting in a total of 67 respondents. The results show that, in terms of social conditions, tubo belerang has significantly affected the social interactions, family welfare, and quality of life of KJA farmers, while the impact on their social participation was less significant. Regarding economic conditions, tubo belerang has had a significant impact on KJA farmers’ production, income, and asset ownership, whereas the effect on their savings and debts was less significant. Concerning the factors influencing KJA farmers’ persistence, the findings reveal that all identified factors are dominant reasons why farmers continue their operations. These factors include internal aspects such as economic considerations and risk management capabilities, as well as external aspects like social support and resource optimization.